The Philosophy of Kuda Leupas ti Gedogan: An Analysis of the Religious Deviation of Students in Ormas-Based Islamic Boarding Schools in Garut Regency - Tohari, Heri Mohamad; Layinah, Leni; Resiana, Gina; Qoyyimah, A. Sofi; Ahmad, Soni (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2025)
This study aims to determine the religious deviation that occurs in several Islamic boarding schools under the auspices of Islamic community organizations (Ormas) in Garut Regency. The focus of the study is directed at the forms of behavioral deviations of students in four Islamic boarding schools affiliated with organizations: Nahdlatul Ulama (NU), Muhammadiyah, Persatuan Islam (Persis), and Syarikat Islam (SI). The method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The results of the study indicate that in the four Islamic boarding schools, similar forms of religious deviation were found, which the local community calls